2019
DOI: 10.1021/acsbiomaterials.9b00218
|View full text |Cite
|
Sign up to set email alerts
|

N-Hydroxysuccinimide Bifunctionalized Triblock Cross-Linker Having Hydrolysis Property for a Biodegradable and Injectable Hydrogel System

Abstract: The design of biocompatible, degradable, and injectable hydrogel has been attractive for achievement of safe and efficient tissue engineering. Herein, we designed a N-hydroxysuccinimide (NHS) ester-terminated ABA triblock copolymer composed of poly­(ethylene glycol) (PEG) as hydrophilic A segments and poly­(dl-lactide) (PLA) as B segment having hydrolysis property (NHS-PEG-b-PLA-b-PEG-NHS) to be a cross-linker of polymer segments having amine groups for facile construction of injectable and degradable hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
4
18
0
Order By: Relevance
“…To investigate the degradation behavior of CH/PEG and CH/PEG‐PLA‐PEG as a cell culture scaffold, weight loss of the hydrogels with encapsulating chondrocytes was traced. Note that this hydrogel system showed nontoxicity and good cell dispersion during the gelation process . CH/PEG‐PLA‐PEG showed higher weight loss compared to CH/PEG in all the periods [Figure (a)].…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…To investigate the degradation behavior of CH/PEG and CH/PEG‐PLA‐PEG as a cell culture scaffold, weight loss of the hydrogels with encapsulating chondrocytes was traced. Note that this hydrogel system showed nontoxicity and good cell dispersion during the gelation process . CH/PEG‐PLA‐PEG showed higher weight loss compared to CH/PEG in all the periods [Figure (a)].…”
Section: Resultssupporting
confidence: 64%
“…In our previous report, we confirmed that the mixtures of CH solution with NHS–PEG–NHS and NHS‐PEG‐ b ‐PLA‐ b ‐PEG‐NHS solutions formed hydrogels within minutes through the reaction of the amine group of CH and the succinimide group of the crosslinkers . CH/PEG‐PLA‐PEG showed accelerated degradability in physiological conditions compared to CH/PEG due to the hydrolysis property of the PLA segment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations